2004
DOI: 10.1086/380431
|View full text |Cite
|
Sign up to set email alerts
|

The Most Likely Sources of High‐Energy Cosmic‐Ray Electrons in Supernova Remnants

Abstract: Evidence of nonthermal X-ray emission and TeV gamma rays from supernova remnants (SNRs) have strengthened the hypothesis that primary Galactic cosmic-ray electrons are accelerated in SNRs. High-energy electrons lose energy via synchrotron and inverse Compton processes during propagation in the Galaxy. Because of these radiative losses, TeV electrons liberated from SNRs at distances larger than $1 kpc, or times older than $10 5 yr, cannot reach the solar system. We investigated the cosmic-ray electron spectrum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
308
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(330 citation statements)
references
References 53 publications
11
308
1
Order By: Relevance
“…As Fig. 1 shows, a simple power-law fit of the Fermi-LAT electron energy spectrum is possible giving: J e ± = (175.40 ± 6.09) E 1 GeV −(3.045±0.008) GeV −1 m −2 s −1 sr −1 (1) with χ 2 = 9.7 (for 23 d.o.f.) where statistical and systematic (dominant) errors have been, conservatively, added in quadrature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Fig. 1 shows, a simple power-law fit of the Fermi-LAT electron energy spectrum is possible giving: J e ± = (175.40 ± 6.09) E 1 GeV −(3.045±0.008) GeV −1 m −2 s −1 sr −1 (1) with χ 2 = 9.7 (for 23 d.o.f.) where statistical and systematic (dominant) errors have been, conservatively, added in quadrature.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to 2008, the high energy electron spectrum was measured by balloon-borne experiments (Kohayashi et al 2004 [1]) and by a single space mission AMS-01 (Aguilar et al 2002 [2]). Those data are compatible with a featureless power-law spectrum within their errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, Table 1) have been interpreted in a number of different ways. Atoyan et al (1995) considered the overall electron spectrum as the sum of a Galactic average and a single source component, and Kobayashi et al (2001) concluded that Vela (distance 250 pc, age 20 kyr) should have produced this component. However, Guetta & Amato (2003) emphasized that the high-energy photons coming from Vela are likely produced by hadronic processes instead of inverse Compton scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible source could be the Monogem pulsar ( Thorsett et al 2003), whose distance and age match the prediction of the model by Erlykin & Wolfendale (1997), who attributed the knee feature to a single nearby source. A few other nearby supernova remnants are considered by Kobayashi et al (2004). Pohl & Esposito (1998) considered the measured spectrum as the superposition of many ''single-source'' components, producing several spectral breaks and a time-dependent electron spectrum.…”
Section: Introductionmentioning
confidence: 99%